Research and trends in the field of technology-enhanced learning from 2006 to 2011: A content analysis of quick response code (QR-code) and its application in selected studies - Goh, Bak Hau; Siraj, Saedah; Alias, Norlidah; Abd Rauf, Rose Amnah; Zakaria, Abd Razak; Darusalam, Ghazali (2012)
This study provides a content analysis of selected articles in the field of QR code and its application in educational context that were published in journals and proceedings of international conferences and workshops from 2006 to 2011. These articles were cross analysed by published years, journal, and research topics. Further analysis was carried out according to research settings, participants, research design types, research methods and findings. It was found from analysis that QR code technology cover a wide range of applications such as augmented reality game, science education, student assignment submission, library catalogue system, communication tools in large classroom environment, system for learning language, collaborative mapping and knowledge management environment, multimedia access tools, assessment tools and so forth. Although the technology covers a wide range of applications, the reported effectiveness of QR technology was not conclusive as most of the data were self-reported such as from questionnaire survey. Most of the studies involved short term research which would not be sufficient to address the complexity of technology integration in educational settings. Hence, it is suggested that future studies should consider offering more reliable and richer findings through longitudinal study and providing inter-observer and intra-observer agreement reliability.